The role of esthetic education in the harmonic development of pre-school children - Helen V. Butina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
In the paper the problems of the modern approach to the development of the emotional sphere of pre-school children are analyzed. Because of the rapid growth of new technologies, usage on Internet, various gadgets and computers in all spheres of life, the need for esthetics is becoming weak. Due to this the development of harmonious personality, esthetically developed people, attentive to spiritual values from the childhood, who can understand and value art, is practically impossible. Because of the progressive decline of spiritual communication between people it is especially important to pay attention to the development of children’s speech. And as a consequence of all other creative abilities: voices, movement, gestures, interests, consciousness, imagination, tastes of children that forms the basics of their culture and contributes to the intellectual and psychological development of children.